2017
DOI: 10.1108/el-04-2016-0080
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Chinese users’ switching behaviour of cloud storage services

Abstract: Purpose This paper aims to explore the switching intention and behaviour of cloud storage services (CSS) individual users in China by integrating the variables of switching cost and habit into the expectation disconfirmation theory. Design/methodology/approach Based on 419 valid responses, structural equation modelling was used to examine the research model. Findings The results indicated that perceived usefulness and expectation disconfirmation have a positive and negative effect on user satisfaction, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…Yuvaraj (2016) explored the perceptions of librarians towards CC and found that they want to adopt CC in the libraries to improve library services. Xu et al (2017) explored the intention and behaviour of using cloud among individual users in China and found that perceived usefulness positively affects to use cloud. Wang et al (2017) revealed that attitude toward cloud using e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yuvaraj (2016) explored the perceptions of librarians towards CC and found that they want to adopt CC in the libraries to improve library services. Xu et al (2017) explored the intention and behaviour of using cloud among individual users in China and found that perceived usefulness positively affects to use cloud. Wang et al (2017) revealed that attitude toward cloud using e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cloud storage is an emerging internet-based storage technology that is changing the information technology (IT) landscape (Xu et al, 2017). The emergence of cloud storage technology is made possible with the innovation of cloud computing which is redefining the IT infrastructure provisioning model from in-house hosted infrastructure and application services to remote hosted service model.…”
Section: Introductionmentioning
confidence: 99%
“…Cloud storage is one of the fundamental technologies of cloud computing technology which enables an organisation to leverage the collaborative capabilities of cloud computing (Xu et al, 2017;Ding and Xu, 2014). It provides scalability in a virtualised environment (Ju et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations